2020
DOI: 10.3390/ijerph17082938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Formal Care Use on Informal Care from Children after the Launch of Long-Term Care Insurance in Shanghai, China

Abstract: The impact of formal care (co-paid by long term care (LTC) insurance) on informal care is critical to the improvement and promotion of public policy. We conducted an interview-based survey to examine how the use of formal care impacts the use of informal care in Shanghai, which was one of China’s first long-term insurance pilots in 2016. In addition to total informal care time, the following four types of informal care were considered: (1) household activities of daily living (HDL) tasks, (2) activities of dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…In addition, on the effect of China’s LTCI policy, scholars have mainly focused on the economic effect. Moreover, as the policy beneficiary groups in the pilot areas are mainly severely disabled individuals, [ 36 , 37 ] ignored the health effect of LTCI policy, and the improvement of health quality is one of the most direct objectives of LTCI. Therefore, we consider the first batch of national LTCI pilot areas as the main study body, based on the three phases tracking survey data of China Health and Retirement Longitudinal Study (CHARLS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, on the effect of China’s LTCI policy, scholars have mainly focused on the economic effect. Moreover, as the policy beneficiary groups in the pilot areas are mainly severely disabled individuals, [ 36 , 37 ] ignored the health effect of LTCI policy, and the improvement of health quality is one of the most direct objectives of LTCI. Therefore, we consider the first batch of national LTCI pilot areas as the main study body, based on the three phases tracking survey data of China Health and Retirement Longitudinal Study (CHARLS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al (2020) 39 conducted an interview-based survey to study the impact of LTCI on informal care in Shanghai. LTCI was associated with a reduction of a weekly average of 12.36 hours of informal care (including household activities of daily living [HDL] tasks, activities of daily living [ADL] tasks, instrumental activities of daily living [IADL] tasks and supervision tasks) in 407 families.…”
Section: Resultsmentioning
confidence: 99%
“…CNKI=China National Knowledge Infrastructure Based on these comprehensive criteria, six studies which all used regression analysis and had a sample size less than 10,000 participants were rated low evidence quality, including Qi et al ( 2019), 37 Zhang et al (2020), 39 Zhang et al ( 2019), 40 Chen et al (2020), 41 Dai et al ( 2019), 42 and Zhang (2019). 43 Two studies, Feng et al (2020) 36 and Ma et al (2019), 38 were classified as having medium evidence quality as they utilized a difference-in-differences design and had a sample size greater than 10,000 participants.…”
Section: Figure 1 Systematic Review Study Selection Flow Diagrammentioning
confidence: 99%
“…To date, only two studies have examined the policy effect on informal care use in China (Lei et al, 2022; Zhang et al, 2020). Zhang et al (2020) found that each additional hour of formal care provided by the LTCI brought about a reduction of 0.47 hours of informal care in Shanghai City, China. As the study was based on retrospective data and did not have a control group, it could not exclude changes in informal care use caused by unobserved factors, such as positive attitudes toward formal care.…”
Section: Formal and Informal Care: A Literature Reviewmentioning
confidence: 99%